Enhancing Arabic Speaking Skills via ChatGPT: An Exploratory Study at Nahdlatul Ulama Sunan Giri University - Kholid, Ahmad Amirul; Majeed, Muhamamd Yasir (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
Mastery of mahārah kalām (speaking skills) is a primary objective in Arabic pedagogy, yet students frequently encounter challenges such as limited vocabulary, psychological barriers, and insufficient interactive practice. In many Indonesian higher education settings, speaking activities are often eclipsed by grammar-centric instruction, resulting in a discrepancy between curricular objectives and oral proficiency. This study investigates the integration of ChatGPT as an AI-driven conversational tool to bridge this gap at Universitas Nahdlatul Ulama Sunan Giri (UNUGIRI). Employing a qualitative exploratory design, the research engaged twenty intermediate-level students from the Arabic Language and Literature Program. Data were synthesized through in-depth interviews, standardized speaking rubrics, and longitudinal learning protocols. The findings demonstrate that ChatGPT significantly enhances fluency, grammatical precision, and communicative confidence by providing a responsive, low-anxiety environment for iterative practice. Furthermore, the AI's immediate feedback serves as a scaffold for independent oral development. This research addresses a critical gap regarding AI-mediated Arabic instruction in the Indonesian context. The implications suggest that structured, lecturer-guided integration of ChatGPT can effectively mitigate affective filters and expand interactive opportunities in environments where authentic Arabic immersion is limited.